2020
DOI: 10.1111/cup.13803
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell sarcoma involving skin and showing epidermotropism: A comprehensive review

Abstract: Langerhans cell sarcoma (LCS) is rare and aggressive; patients have an overall survival rate of less than 50%. We present a 62-year-old man with a history of superficial spreading melanoma of the upper back with sentinel lymph node metastasis, Langerhans cell histiocytosis, and LCS. The patient presented with erythematous papules and scaly areas on his face, neck, arms, chest, abdomen, and legs. A skin biopsy revealed a proliferation of large neoplastic cells involving the dermis and with epidermotropism. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…[1][2][3] Diagnosis of primary Langerhans cell sarcoma is difficult, and it is necessary to differentiate it from other malignancies of the skin, including anaplastic large cell lymphoma, 4 malignant melanoma, 5 metastatic cancer, myeloid sarcoma, and malignant fibrous histiocytoma. 6 Langerhans cell sarcoma occurs at any age and involves many organs or tissues, including bone marrow, 7 lung, 8 lymph nodes, 9 liver, 10 skin, [11][12][13] and subcutaneous tissue. 14 Our case indicated that the differential diagnosis of Langerhans cell sarcoma should be borne in mind for cases with high FDG uptake of skin mass.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] Diagnosis of primary Langerhans cell sarcoma is difficult, and it is necessary to differentiate it from other malignancies of the skin, including anaplastic large cell lymphoma, 4 malignant melanoma, 5 metastatic cancer, myeloid sarcoma, and malignant fibrous histiocytoma. 6 Langerhans cell sarcoma occurs at any age and involves many organs or tissues, including bone marrow, 7 lung, 8 lymph nodes, 9 liver, 10 skin, [11][12][13] and subcutaneous tissue. 14 Our case indicated that the differential diagnosis of Langerhans cell sarcoma should be borne in mind for cases with high FDG uptake of skin mass.…”
Section: Figurementioning
confidence: 99%
“…Development usually occurs at 30-40 years of age; however, the disease may have a wider age of onset and may also present in children [4,5]. LCS affects multiple organ systems; however, previously published literature has identified the skin, lymph nodes, bone marrow, lungs, spleen, and liver as common sites of involvement [6][7][8]. Diagnosis of this disease has proved to be difficult since its marked cytologic atypia and pleomorphism is coherent with several other diseases such as malignant melanoma, lymphomas, and other dendritic cell tumors.…”
Section: Introductionmentioning
confidence: 99%